2023
DOI: 10.1111/cid.13206
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and management of peri‐implant disease

Abstract: Background As more patients choose dental implants as their primary treatment option to restore edentulous ridges or to replace compromised dentition, preventive strategies for peri‐implant diseases and complications have become an important topic. Purpose The aim of the review article is to summarize the current available evidence on the potential risk factors/indicators for peri‐implant disease development and then focus on the preventive strategies for peri‐implant diseases and conditions. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 174 publications
0
3
0
Order By: Relevance
“…Especialmente na Implantodontia, para se garantir um tratamento de sucesso a longo prazo é necessário um registro adequado das informações como tipo de implante e componente protético, associado a um programa de manutenção periódica, com retornos frequentes do paciente, sendo indicado um retorno a cada 3 meses no primeiro ano e nos anos subsequentes esse retorno deve ser calculado com base nos fatores de risco apresentados (Sun, Chen & Gallucci, 2023). Dessa forma, trata-se de uma área que pode se beneficiar muito dos avanços tecnológicos para subsidiar suas práticas de gestão.…”
Section: Referencial Teóricounclassified
“…Especialmente na Implantodontia, para se garantir um tratamento de sucesso a longo prazo é necessário um registro adequado das informações como tipo de implante e componente protético, associado a um programa de manutenção periódica, com retornos frequentes do paciente, sendo indicado um retorno a cada 3 meses no primeiro ano e nos anos subsequentes esse retorno deve ser calculado com base nos fatores de risco apresentados (Sun, Chen & Gallucci, 2023). Dessa forma, trata-se de uma área que pode se beneficiar muito dos avanços tecnológicos para subsidiar suas práticas de gestão.…”
Section: Referencial Teóricounclassified
“…The primary etiology of peri-implant diseases is microbial infection of the peri-implant tissues [ 183 , 184 ]. Peri-implantitis is characterized by a dysbiosis of the subgingival microbial ecosystem [ 185 ].…”
Section: The Role Of Probiotics Against Peri-implant Diseasesmentioning
confidence: 99%
“…Based on existing research, if left untreated in the early stages, peri-implant mucositis tends to rapidly progress [ 220 ]. Considering the cost and difficulty of treating peri-implantitis, the best approach is to intervene before the onset of peri-implant diseases or in the early stages of the disease to prevent further progression [ 126 , 184 ]. Although probiotics are controversial for the cure of peri-implantitis, more than one study emphasizes the clinical significance of probiotics in controlling and preventing peri-implant diseases [ 105 , 208 , 213 , 221 , 222 ].…”
Section: The Role Of Probiotics Against Peri-implant Diseasesmentioning
confidence: 99%
“…Plus, patients who underwent reconstructive surgery suffer from limitations in oral opening because of oral vestibule contracture, reporting difficulty in accessing the abutments for effective home-care oral hygiene procedures [ 23 ]. As many studies demonstrated that higher plaque levels [ 24 , 25 ] and lack of accessibility for cleaning at implant level [ 21 ] are both significantly associated with peri-implantitis, oral hygiene performed by patients therefore represents a key component in preventing peri-implant diseases [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%